The Quantitative Seismic Analysis of a Precast Reinforced Concrete Frame Hall and the Establishment of Retrofitting Solutions. Part I – The Dynamic Analysis of the Existing Structural System - Sococol Ion; Mihai Petru; Petrescu Tudor-Cristian; Babor Traian-Dănuţ (Bulletin of the Polytechnic Institute of Jassy: Constructions, Architechture Section)
Prefabricated Reinforced Concrete (PRC) frame structures designed and executed in the pre-1989 period in Romania, occupy a leading spot in the list of industrial, commercial, social and cultural buildings. In this research study, a structure of this type is analyzed. In the introductory part of the study, the types of PRC frame systems specific to seismic zones and their component elements are highlighted. The second part shows the main structural deficiencies of the PRC frame structures required to severe earthquakes. In the following chapters, the dynamic analysis related to the studied structure is developed, as well as a verification of the lateral stiffness. Thus, it was found that the PRC structure develops lateral displacements higher than the admissible limit. In these conditions, some solutions are proposed for retrofitting the structural system using vertical steel braced frames, shear walls, steel-RC composite columns and steel beams on the bay direction.